Oral hygiene and smoking habit as risk factors of periodontal disease. - Maricela Seijo Machado; Marta M. Bosch Pons; Esther M. Castillo Betancourt; Sahily Espino Otero; Alicia Quiñones Betancourt (Medisur)
Background: Peridontal diseases are among the most common diseases affecting human beings, and these are more frequent after the age of 35. Smoking habit is one of the risk factors usually linked with the development of these diseases. Objective: To characterize the relation between periodontal condition and buccal hygiene in patients with smoking habit. Method: Descriptive, cross-sectional, epidemiological study including 95 smokers from Palmira municipality; January-November, 2007. Peridontal treatment index was used in the community, as well as the simplified buccal hygiene index. Results: There was high prevalence of periodontal disease (85, 2%); buccal hygiene was directly related with smoking habit. Conclusions: The study shows an important relation between the periodontal disease in smokers, buccal hygiene and smoking habit intensity.